UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DENGAN MENGGUNAKAN METODE PEMBERIAN TUGAS DAN RESITASI PADA KELAS XI IPA-1 SMAN NEGERI 1 LEMBAH MELINTANG - midrawati midrawati (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on student learning outcomes 1st Class XI IPA SMAN 1 Valley Crossing in Mathematics was found that student learning outcomes in mathematics is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in mathematics through Giving Methods Tasks and recitation in Class XI-1 SMAN 1 Valley Crossing West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 38 learners Class XI Science 1 SMAN 1 Valley Crossing. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the method of administration of Tasks and recitation can improve student learning outcomes in mathematics at SMAN 1 Valley Melintng. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 72.8 increased to 82.29 (good) with an increase of 6.50%.